Protective Effects of Pituitary Adenylate Cyclase-Activating Polypeptide and Vasoactive Intestinal Peptide Against Cognitive Decline in Neurodegenerative Diseases - Solés-Tarrés, Irene; Cabezas-Llobet, Núria; Vaudry, David; Xifró, Xavier (Frontiers in Cellular Neuroscience, 2020)
Cognitive impairment is one of the major symptoms in most neurodegenerative disorders such as Alzheimer's (AD), Parkinson (PD) and Huntington (HD) diseases, affecting millions of people worldwide. Unfortunately, there is no treatment to cure or prevent the progression of those diseases. Cognitive impairment has been related to neuronal cell death and/or synaptic plasticity alteration in important brain regions, such as cerebral cortex, substantia nigra, striatum and hippocampus. Therefore, compounds that can act to protect the neuronal loss and/or to reestablish the synaptic activity are needed to prevent cognitive decline in neurodegenerative diseases. Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) and Vasoactive Intestinal Peptide (VIP) are two highly related multifunctional neuropeptides widely distributed in the Central Nervous System. PACAP and VIP exert their action through two common receptors, VPAC1 and VPAC2, while PACAP has an additional specific receptor, PAC1. In this review we first presented evidences showing the therapeutic potential of PACAP and VIP to fight the cognitive decline observed in models of AD, PD and HD. We also reviewed the main transduction pathways activated by PACAP and VIP receptors to reduce cognitive dysfunction. Furthermore, we identified the therapeutic targets of PACAP and VIP, and finally we evaluated different novel synthetic PACAP and VIP analogues as promising pharmacological tools.